Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1590/fst.57520
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant dietary fiber-based bakery products: a new alternative for using plant-by-products

Abstract: Agro-industrial processing activities generate by-products that are discarded at high economic and environmental costs; however, many of them still contain high levels of bioactive compounds (BCs) such as dietary fiber (DF) and phenolic compounds (PCs), which, when combined, are known as antioxidant dietary fiber (ADF). These BCs have properties that are beneficial to our health, among them anti-inflammatory, antioxidant and cardioprotective. Moreover, DF can regulate glucose and cholesterol levels. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 85 publications
0
16
0
1
Order By: Relevance
“…Due to this characteristic, studies have been developed that add phenolic compounds to bread, to compensate for the loss of fiber and germ and increase the antioxidant activity present in bakery products. However, several authors have found that the addition of these compounds produces relevant changes in the structure and sensory characteristics of bread (Xu et al 2019, Subiría-Cueto et al 2021), as will be discussed in the following sections. Bread making process consists in mixing wheat flour, water, salt, sugar, and yeast.…”
Section: Structure and Characteristic Of Wheat Breadmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this characteristic, studies have been developed that add phenolic compounds to bread, to compensate for the loss of fiber and germ and increase the antioxidant activity present in bakery products. However, several authors have found that the addition of these compounds produces relevant changes in the structure and sensory characteristics of bread (Xu et al 2019, Subiría-Cueto et al 2021), as will be discussed in the following sections. Bread making process consists in mixing wheat flour, water, salt, sugar, and yeast.…”
Section: Structure and Characteristic Of Wheat Breadmentioning
confidence: 99%
“…When spice extracts were used, the sensory characteristics were even better. On the other hand, the addition of flours obtained from by-products rich in phenolic compounds were able to increase antioxidant capacity and fiber content, although in these cases sensory acceptability decreased (Pop et al 2016;Subiría-Cueto et al 2021).…”
Section: Wang Et Al (2014)mentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation in the food industry through the use of biocompounds not only adds to the circular economy sustainability concept but is also an opportunity to attend consumers’ expectations. In fact, consumers’ concern for safer and healthier foods is increasing, and food industry is under pressure to offer healthy, convenient, and ready-to-eat foods, able to meet daily nutritional needs, provide pleasure and satiety, and attend to consumers’ expectations and safety issues [ 101 , 102 ]. In this scenario, the replacement of synthetic compounds, generally associated with toxicity and allergenic problems, with healthy natural alternatives is increasingly evident [ 101 ].…”
Section: Value-added Compounds In the Development Of Innovative Food Productsmentioning
confidence: 99%
“…Alongside, the enrichment of products by using compounds with nutritional value is also a growing tendency. The use of agro-industrial residues, rich in bioactive compounds, has been the focus of studies that propose the use of these by-products in the formulation of functional foods [ 102 ]. As synthetized in Table 3 , value-added compounds were recovered from industrial processes wastewater, from commercially unexplored fruits, and industrial processing by-products, and their applicability was verified.…”
Section: Value-added Compounds In the Development Of Innovative Food Productsmentioning
confidence: 99%